PENGARUH MODEL PEMBELAJARAN SELF DIRECTED LEARNING TERHADAP KEMAMPUAN MENULIS PUISI PADA SISWA KELAS XI SMA TAMANSISWA PEMATANGSIANTAR - Eliezer Naibaho, Jhon; Sirait, Jumaria; Tambunan, Marlina; Junifer Siregar; Immanuel Doclas Belmondo Silitonga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This Study Objective: This study aims to determine how active students are in writing poetry after using an independent learning model among eleventh-grade students. This research is a quantitative experimental study with a group pre-test-post-test design. Quantitative research is a systematic investigation of a phenomenon and the collection of measurable data using statistical, mathematical, or computational techniques. The population in this study was 276 students, and a sample of 35 students was drawn using a cluster sampling technique. Data were collected through poetry writing tests before and after the treatment. The results showed that the average pre-test score was 75.97 and increased to 82.91 in the post-test. The t-test results showed that the calculated t-value was higher than the t-table, indicating a significant effect. Thus, the independent learning model is effective in improving students' poetry writing skills.